Fiqh Wakaf: Manajemen dan tantangan wakaf produktif dalam transformasi sosial - Faradila, Dinda Silvy (Maliki Interdisciplinary Journal, 2025)
This study discusses the concept of fiqh waqf and its implementation in the development of productive waqf as an instrument of social transformation. From a fiqh perspective, waqf has a strategic position as a sustainable charitable deed and a basis for strengthening the welfare of the community. However, the optimisation of productive waqf in Indonesia still faces a number of challenges, such as weak management, low public literacy, limited nadzir competence, and a lack of innovation in asset management. This study highlights the importance of a modern management system that is integrated with sharia principles, including planning, asset development, accountability, and transparency. Furthermore, social transformation through productive waqf can be realised if management is carried out professionally, adaptively, and based on community needs. This study concludes that synergy between regulations, the capacity of waqf administrators, and public participation are key factors in strengthening the role of productive waqf as a driver of social change.